Continuous dental replacement in a hyper-chisel tooth digging rodent - Gomes Rodrigues, Helder (National Academy of Sciences, 2011)
Contrary to their reptilian ancestors, which had numerous dental generations, mammals are known to usually develop only two generations of teeth. However, a few mammal species have acquired the ability to continuously replace their dentition by the constant addition of supernumerary teeth moving secondarily toward the front of the jaw. The resulting treadmill-like replacement is thus horizontal, and differs completely from the vertical dental succession of other mammals and their extinct relatives. Despite the developmental implications and prospects regarding the origin of supernumerary teeth, this striking innovation remains poorly documented. Here we report another case of continuous dental replacement in an African rodent, Heliophobius argenteocinereus, which combines this dental system with the progressive eruption of high-crowned teeth. The escalator-like mechanism of Heliophobius constitutes an original adaptation to hyper-chisel tooth digging involving high dental wear. Comparisons between Heliophobius and the few mammals that convergently acquired continuous dental replacement reveal that shared inherited traits, including dental mesial drift, delayed eruption, and supernumerary molars, comprise essential prerequisites to setting up this dental mechanism. Interestingly, these dental traits are present to a lesser extent in humans but are absent in mouse, the usual biological model. Consequently, Heliophobius represents a suitable model to investigate the molecular processes leading to the development of supernumerary teeth in mammals, and the accurate description of these processes could be a significant advance for further applications in humans, such as the regeneration of dental tissues.